Pulsed Er,Cr:YSGG Laser For Surface Modification of Dental Zerconia Ceramic - Muhammed, Fateema Sameer; Jawad, Hussein Ali (Iraqi Journal of Laser, 2021)
Background: Surface treatment of machined dental zirconia for enhancement of the adhesion to resin cement, using Er,Cr:YSGG  Laser. Materials and Methods: Total number of 42 zirconia disc specimens (9 mm diameter, and 2 mm height) was sintered according to the manufacturer instruction. They are divided into six groups, each group of seven samples. Laser groups (Experiment parameters) were depend on laser total irradiation time, pulse duration, and power. Group (A): 20 sec., 60 µs pulse duration. Group (B): 30 sec., 60 µs pulse duration. Group (C): 40 sec., 60 µs pulse duration. Group (D): 20 sec., 700 µs pulse duration. Group (E): 30 sec., 700 µs pulse duration, with different powers used (1, 1.50, 2, 2.50, 3, 3.50, 4) W. And finally group (N): untreated samples representing the control group. Luting cement was applied to laser treated zirconia sample’s surfaces and cured by light for 40 s. Then all sample surfaces were examined under a stereo microscope, for determining the depth mean values of the created pulse holes, for each specimen. The bond between the laser treated zirconia surfaces and the applied resin cement, were examined for all samples by using a universal testing machine, for determination of the shear bond strength values. Six additional specimens: one untreated sample and five other samples that were laser irradiated with the parameters that exhibited the highest shear bond strength values in each treated group, were examined for their average surface roughness by using an atomic force microscope. Another similar six specimens were also examined for their surface morphology, by using a scanning electron microscope. Both surface examination methods were performed by specialized operators. The bond failure modes were also examined by an optical microscope. Results obtained from shear bond strength test and laser pulse depth examination were statistically analyzed. Results: There was significant differences in the shear bond strength values, indicating a clear increase in zirconia-resin cement bonding, especially in group B (30 s, 60 µs, 4W), reaching  (8.63 Mpa). Whereas, the control group had (4.49 Mpa), and an enhanced zirconia surface average roughness, that group E (30 s, 700 µs, 3.5 W) specimen had the highest value (14.5nm), among the six examined specimens. While the control specimen had the least value examined which is (3.05nm). Conclusion: A relation between the cement bonding efficiency and the laser treated zirconia surface roughness, laser pulse depths was detected. The Er,Cr:YSGG laser pulse duration and  power is  crucial parameters in the surface roughness enhancement of the zirconia ceramic.